Reliability of demand-based phased-mission systems subject to fault level coverage - Peng, Rui; Zhai, Qingqing; Xing, Liudong; Yang, Jun (Reliability engineering & system safety, 2014)
In many real-world applications, a mission may consist of several different tasks or phases that have to be accomplished in sequence. Such systems are referred to as phased-mission systems (PMS). In this paper we consider the demand-based PMS with parallel structure, where the system components function in parallel with different capacities in each phase of the mission and the mission is successful if and only if the total system capacity meets the predetermined mission demand in each phase. The reliability of the demand-based PMS (DB-PMS) with parallel structure subject to fault-level coverage (FLC) is first studied using a multi-valued decision diagram (MDD) based technique. The traditional MDD is modified to accommodate the FLC mechanism and new MDD construction and evaluation procedures are proposed for DB-PMS. To reduce the size of the MDD, an alternative construction procedure applying the branching truncation method and new reduction rules are further proposed. An upwards algorithm is put forward to evaluate the reliability of DB-PMS subject to FLC. The proposed approaches are illustrated through examples. •Reliability of phased-mission systems subjected to fault level coverage is studied.•System demand and component stress change from phase to phase.•A combinatorial method based on multi-valued decision diagrams is proposed.